Climatic discrimination of Mediterranean broad-leaved sclerophyllous and deciduous forests in central Spain (Journal of Vegetation Science, 1997)
Abstract. Climatic differences between three types of deciduous (Quercus pyrenaica) and three types of sclerophyllous (Quercus rotundifolia) Mediterranean forests in the Spanish Sistema Central were analyzed by means of Canonical Discriminant Analysis and Jancey's Discriminant Analysis, applied in successive steps to data from 252 meteorological stations. Climatic data included temperature and precipitation records as well as bioclimatic indices. Discriminant analysis was applied to broad-leaved sclerophyllous and deciduous forest communities sampled at each meteorological station using phytosociological methods. Annual and seasonal (summer, spring) water availability are the most important factor controlling the distribution of the two physiognomic forest types; southwestern associations of Quercus pyrenaica and Q. rotundifolia differ from their colder homologues by annual and monthly temperatures; western associations were separated from eastern ones in terms of annual and seasonal precipitation gradients. Discriminant analysis was a good technique to explore climatic gradients not shown by other general ordination or classification methods.